ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MATA KULIAH KONSTRUKSI BANGUNAN - Ahmad Zaidan Rofif (CV. ADIBA AISHA AMIRA, 2024)
The shift from Teacher Centered Learning (TCL) towards Student Centered Learning (SCL) demands that learners become subjects with the potential to explore their abilities and knowledge to be more active, creative, and independent in the learning process. Therefore, educators are required to choose the appropriate learning models to make students more active, creative, and independent in their learning activities, particularly in the field of building construction courses. Project Based Learning (PBL) is a model in which students play an active role in creating a project or product relevant to their competencies. This research aims to analyze the extent of the influence of project-based learning models on building construction courses in vocational education. The method used in this research is a literature review, focusing on examining and analyzing several journals and articles related to the title I have created. Through comprehensive analysis of several relevant journals and articles, this article identifies the positive and negative impacts of PBL on building construction courses, aiming to provide insights for educators and researchers in determining effective learning models.